Nutrient Removal in the Treatment of Batik Wastewater using Bench-Scale Sequencing Batch Reactor (SBR) System - Ng , Jia Yi (Universiti Teknologi PETRONAS, 2020)
Batik is one of the oldest cottage textile industries in Malaysia. Kilang Batik Fauzi, a local batik factory located in Chemor, Perak Darul Ridzuan, Malaysia, has been operating for batik production and served as a tourist attraction for almost two decades. The batik factory discharges the batik wastewater produced during the batik process, includes soaking, boiling, and rinsing steps into the ground without proper treatment. The lack of appropriate treatment for batik wastewater has always been a significant problem developed by most batik factories. Kilang Batik Fauzi discharges its effluents into the environment without proper treatment, providing negative impacts on the environment and ecosystems due to toxicity and non-biodegradability of chemicals, and dyes present in batik discharges.